Splenic Infarction with Myocardial Injury in a Diabetic Patient: A Case Report - Wang C; Wen S; Zhou L (Diabetes, Metabolic Syndrome and Obesity, 2023)
Congcong Wang,1 Song Wen,1 Ligang Zhou1,2 1Department of Endocrinology, Shanghai Pudong Hospital, Fudan University, Shanghai, 201399, People’s Republic of China; 2Shanghai Key Laboratory of Vascular Lesions Regulation and Remodeling, Shanghai Pudong Hospital, Fudan University Pudong Medical Center, Shanghai, People’s Republic of ChinaCorrespondence: Ligang Zhou, Department of Endocrinology, Shanghai Pudong Hospital, Fudan University, Shanghai, 201399, People’s Republic of China, Tel +86 13611927616, Email zhouligang@yahoo.comAbstract: Splenic infarction (SI) is an uncommon complication of type 2 diabetes (T2D). Diabetes predisposes individuals to blood vessel abnormalities, such as atherosclerosis or thrombosis, increasing the risk of vessel occlusion and subsequent tissue infarction. If the diabetic patient has other serious diseases, such as a severe pneumonia infection and acute cardiac infarction, SI incidence may go unrecognized, making it challenging for physicians to identify. This case report discussed an 80-year-old hospitalized diabetic woman with a history of chronic bronchitis and 20 years of T2D who suffered an SI. The patient was at elevated risk for thrombosis of atrial fibrillation, manifested as an embolism of the spleen characterized by a high concentration of white blood cells. This patient also demonstrated a rapid increase in cardiac biomarkers troponin I, suggesting acute myocardial infarction (AMI) and increased amylase, which could not preclude the concern about the existence of acute pancreatitis. Abdominal CT displayed the calcification of only the splenic and other arteries, and low-density shadows were observed at the center portion of the spleen. This case demonstrated the significant occurrence of thrombotic complications in various blood vessels of multiple organs in T2D patients. Thus, clinicians should be aware of the possibility of simultaneous acute vascular infarction of several organs in diabetic patients with prior vascular constriction.Keywords: systemic thrombosis, splenic artery embolism, spleen infarction, type 2 diabetes